Synthesis and characterization of carbon molecular sieve CMK-3 - Thao, Nguyen Tien (VNU Journal of Science: Natural Sciences and Technology; Vol 27 No 4, 2011)
Abstract. A nanoporous carbon material was prepared using silica SBA-15 as a template and characterized by several techniques: XRD, N 2 -adsorption/desorption, SEM, and TEM. Carbonaceous material exhibits typical characteristics of nanostructed carbon family. The specific surface area and the mean pore size are about 1400 m 2 /g and 4 -12 nm, respectively. Keywords: CMK-3, mesopores, carbon molecular sieve.